MINORITISASI AHMADIYAH DI INDONESIA - Amin Mudzakkir (Kedeputian Bidang Ilmu Sosial dan Kemanusiaan (IPSK-LIPI), 2011)
This article shows the process of minoritization of Ahmadiyya in Indonesia.This is a phenomenon of the post-Suharto regime. Under the currentIndonesias liberal democratic system, the existence of minority groups is oftenmarginalized because they are considered not important for political party towin the election. Minoritization occurs when two conditions are met, namelythe strengthening of radical Islamic groups and the seemingly indecisivebehavior of government to deal with radicalism. The paper critically looksat the current Indonesia political system in order to look for solution to theAhmadiyya issue.Keywords: minoritization, Ahamdiyya, radical Islam, liberal democracy.